Aplikasi Sistem Pembelajaran Online Dengan Pemanfaatan Situs Jejaring Sosial Facebook Pada Sekolah Menengah Pertama - Mumtahanah, Arniatun Nur; , Prof. Dr. Budi Murtiyasa, M.Kom; , Masduki, S.Si, M.Si (2013)
This research is aimed to describe about usage of Facebook networking site in education sector and prove that Facebook can be use as an online learning media. The subject of this research are head of school, teachers and students 7 grade of SMP Negeri 1 Mojolaban. Observation and interview are use to collect information. The result of this research is interaction between teacher and students which is appear on facebook account and conclusion which can use as measuring compass about students satisfaction in learning with facebook. The students opine that learning with facebook is very interesting and enjoyable because they can diminishing saturation in classroom. And then the students also can interaction with their friend in facebook and share their knowledge with other friend. Meanwhile the teacher opine that online learning with facebook is an inovation in education. Internet are not only can be use as media to look for information but can be use as a online learning media if using optimally. However there are many problems with the students activation, they are only give a little comment and the amount of student who interact is few.